Utility of Botulinum Toxin ELISA A, B, E, F kits for clinical laboratory investigations of human botulism. (17th August 2011) - Maslanka, Susan E.; Luquez, Carolina; Raphael, Brian H.; Dykes, Janet K.; Joseph, Lavin A.
The Botulinum Toxin ELISA effectively provided presumptive identification of toxin in 1381 investigation samples including clinical specimens, suspect foods, and cultures. Additionally, the ELISA detected all toxins produced by a panel of stock strains representing known subtypes and was negative for non-botulinum toxin producing Clostridium and enteric pathogens. ELISA results were reproducible both within the same kit (CV < 9%) and among different production lots (CV < 23%). Fifty-five of 57 laboratories correctly identified unknown samples in a multi-laboratory study. The ELISA provides a rapid, robust in vitro screening method which will reduce animal dependence during laboratory investigations of botulism.